KERJASAMA EKONOMI INDONESIA-CHINA DALAM EKSPOR PRODUK PERIKANAN PADA MASA COVID-19 - Saphira Anindhita Putri Pratama, (2023)
This research explains the cooperation between Indonesia and China in the export of fishery products through the Ministry of Maritime Affairs and Fisheries (KKP) and the General Administration of Customs of the People's Republic of China (GACC). The purpose of this research is to see how Indonesia can optimize in carrying out Indonesia-China cooperation with Decree no. 103 of 2020. In this study, it provides an explanation regarding how the Indonesian Government's efforts to face the challenges of Indonesia-China economic cooperation during the Covid-19 period in the export of fishery products. In 2019-2021 the covid-19 virus spread in various parts of the world, causing a sizeable impact on every sector, including exports of Indonesian fishery products. China is a country that is one of the biggest importers for Indonesia. China itself tightened its import activities by issuing Decree No. 103 of 2020 regarding tightening of fishery products. This study uses a qualitative research method with data collection techniques in the form of interviews and assisted by literature. This study was analyzed using the theory of bilateral economic cooperation. The results of the research in this thesis show the efforts that have been made by Indonesia in overcoming obstacles to the existence of Decree no. 103 of 2020, has had a significant impact. In the data shown, Indonesia's export of fishery products to China continues to run well without a significant decline. Keywords: Ministry of Maritime Affairs and Fisheries (KKP), Administration of Customs of the People's Republic of China (GACC), Export of Fishery Products, Bilateral Cooperation.